STUDY OF THE EFFECT OF CHEMICAL POLLUTION WITH COALFIRED POWER PLANT ON THE FISH OF LAKE KENON (TRANS-BAIKAL TERRITORY, RUSSIA) - Tsybekmitova, Gazhit Ts.; Gorlacheva, Evgeniya P.; Tashlykova, Nataliya A. (Quaestiones Geographicae, 2021)
In this study, contamination of potentially toxic elements (Cr, Mn, Cu, Zn, Hg and Pb) and species dominant in the fish community of Lake Kenon – Carassius auratus gibelio (Bloch 1782) and Perca fluviatilis (Linnaeus 1758) – were investigated. Chemical elements in samples were determined by atomic emission spectrometry (iCAP-6500, Thermo Scientific, USA) and mass spectrometry (X-7, Thermo Elemental, USA). It was reported that water in Lake Kenon contained low concentrations of the studied metals. The bottom sediments are enriched with Mn, Zn, Hg and Pb. Bioaccumulation factors of chemical elements accumulated from the surrounding water for P. fluviatus and C. auratus gibelio in descending order are as follows: Zn > Pb > Hg > Cu. P. fluviatus accumulates Hg in equal measure from both water and bottom sediments. Manganese and mercury are accumulated in the muscles of C. auratus gibelio from bottom sediments. The high accumulation ratio of Zn and Hg in C. auratus gibelio was obtained from Chara sp. (24 times) and Chironomus spp. (38 times), respectively. High accumulation ratio of Zn (26 times) and Hg (29 times) in P. fluviatus was obtained from amphipods. At the same time, Hg in P. fluviatus muscles was accumulated at high level from Chironomus spp. (67 times). In this way, management decisions for mitigation practices in Lake Kenon should be focussed on for the disposal of wastewater from the ash dump contaminated with chemical elements.